1998
DOI: 10.1108/13552549810223000
|View full text |Cite
|
Sign up to set email alerts
|

Online functional testing with rapid prototypes: a novel empirical similarity method

Abstract: With over forty years' experience, Emerald Group Publishing is a leading independent publisher of global research with impact in business, society, public policy and education. In total, Emerald publishes over 275 journals and more than 130 book series, as well as an extensive range of online products and services. Emerald is both COUNTER 3 and TRANSFER compliant. The organization is a partner of the Committee on Publication Ethics (COPE) and also works with Portico and the LOCKSS initiative for digital archiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…A plastic filament is unwound from a coil and supplies material to an extrusion nozzle. Nozzle is heated to melt the plastic has a mechanism which allows the flow of the melted plastic to be turned on and off [21]. The nozzle is mounted to an X-Y plotter type mechanism to trace out the part contours.…”
Section: Details Of Fdm Machinementioning
confidence: 99%
“…A plastic filament is unwound from a coil and supplies material to an extrusion nozzle. Nozzle is heated to melt the plastic has a mechanism which allows the flow of the melted plastic to be turned on and off [21]. The nozzle is mounted to an X-Y plotter type mechanism to trace out the part contours.…”
Section: Details Of Fdm Machinementioning
confidence: 99%
“…At last, synthesising the above derivation obtains the simplified cylindrical shell with axial length l, mid-radius R, thickness H, Young's modulus of elasticity E 1 , shear modulus G sim and density ρ sim . Equations 7, (10) and (21) are the expression of H, ρ sim and G sim , respectively.…”
Section: Process Of Equivalencementioning
confidence: 99%
“…Cho (21) presented and continuously developed a novel empirical similitude method: the empirical similarity method (ESM). By designing product specimen and model specimen as the transitional models, the ESM can deal with some of similarity distortions (22)(23)(24)(25) .…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2009), using data from 273 manufacturing firms, reported that prototypes with high flexibility improve speed and lead to higher customer satisfaction, thus meeting competitive challenges. The application of new technologies has allowed prototyping to shift from conventional physical techniques to virtual, and hence more rapid prototyping (Cho et al, 1998) and web-based systems (Lan, 2009). Ma et al (2007) stressed that, in a manufacturing sector that requires complex designs and stages of development, virtual prototypes constructed using integrated software technology allow for manipulation by virtual assembly and stereoscopic display, all of which facilitate the rapid assessment of the functionality, design robustness and aesthetic appeal of products.…”
Section: Prototyping and New Product Successmentioning
confidence: 99%